Urogenital Tract Infections in Preterm Labour and Preterm Premature Rupture of Membrane- An Observational Study - Sangamesh Sharanayya Mathapati; Aruna Mallangouda Biradar; Preeti Gurulingappa Patil; Mohd Shannawaz; Supriya Hakki (JCDR Research and Publications Pvt. Ltd., 2020)
Introduction: Preterm birth is the leading cause of neonatal morbidity and mortality. One of the major causes for Preterm Labour (PTL) and Premature Rupture of Membrane (PROM) is infection of urogenital tract. Aim: To study the incidence of genitourinary infection in patients with preterm labour and preterm premature rupture of membrane. Materials and Methods: A Prospective study was conducted at BLDE (DU) Shri BM Patil Medical College. We enrolled 100 pregnant women with preterm/preterm PROM in the study and evaluated for the genitourinary infection by doing urine culture, cervical swab culture, vaginal swab culture and examination of urine for pus cells. The participants were given appropriate obstetric care and followed till delivery. Results: In the present study, study the incidence of genitourinary infection in preterm/preterm PROM was 59%. The cervical swab was positive in 33 participants, the vaginal swab was positive in 26 participants, the urine culture was positive in 19 participants, 35 participants had significant pus cells indicating urinary tract infection. A total of 59 participants had one or the other form of genitourinary infection. Out of the 100 participants enrolled in the study, 82 patients continued the pregnancy till full term. Conclusion: Genitourinary infection is highly prevalent among patients of Preterm labour/preterm PROMs. There is a need for educating pregnant women regarding personal hygiene to prevent the genitourinary infections.